5 - Vers une économie politique des conflits au ras du sol: 10.4314/ad.v24i3.22128 - Jean-Marc Ela (Africa Development, 1999)
To what extent is conflict central to the day-to-day life in Africa, where millions of men and women are confronted with the crises of the state and economy as a result of adjustment and globalization processes underway? The paper highlights that the dynamics of violence are deeply rooted in the day-to-day life and sheds light on the crises undermining the very foundations of African societies. It argues that such an understanding forces us to recognise the 'disenchantment' process unfolding in contemporary Africa, revisit the logics of frustration and exclusion affecting weakened communities (populations) and to grasp the origins of the conflicts in Africa to day.